AB0792 Bone mineral density and seasonal variations in bone turnover in systemic sclerosis patients. (23rd January 2014) - Seriolo, B.; Botticella, G.; Paolino, S.; Casabella, A.; Sulli, A.; Molfetta, L.; Pizzorni, C.; Cutolo, M.
Abstract : Background: Systemic sclerosis (SSc) is characterised by microvascular involvement and fibrosis of the skin and internal organs 1 . Objectives: In this study, bone mineral density (BMD) and parameters of bone turnover were evaluated to investigate the presence of systemic osteoporosis and/or osteopenia in SSc patients on the basis of their nailfold videocapillaroscopy (NVC) patterns of microangiopathy ("early", "active", and "late") 2 . Methods: 42 patients (mean age 59±9 years) affected by SSc and presenting the "early" n=5; "active" n=9 and "late" n=28 NVC patterns as well as 36 age-matched healthy controls (mean age 61±3 years) were studied after informed consent. BMD of the lumbar spine (L1 -L4 ) and the proximal femur was analyzed using dual-energy X-ray absorptiometry (DXA) scan (Lunar Prodigy, GE, USA).Spot urinary calcium/creatinine ratio, and urinary deoxypyridinoline (Dpd) and crosslinks (NTx) were measured. Serum levels of phosphorus, calcium, bone alkaline phosphatase (bALP), osteocalcin (OC), as well as 25-hydroxyvitamin D [25(OH)D] were analyzed during winter and summer. Results: Of the 32 SSc patients enrolled, 28 (87%) presented bone loss, and in particular 10 (31%) showed densitometric osteoporosis and 18 (56%) had osteopenia. BMD was significantly lower in the SSc patients than in the control group (lumbar spine: 0.979±0.120 g/cm 2 vs 1.153±0.132 g/cm 2, p<0.001; femoral neck 0.734±0.104 g/cm 2 vs 0.877±0.128 g/cm 2, p<0.0001; Ward 0.545±0.085 g/cm 2 vs 0.071±0.125 g/cm 2, p<0.0001; trochanter 0.669±0.107 g/cm 2 vs 0.774±0.187 g/cm 2, p<0.005; total hip 0.802±0.008 g/cm 2 vs 0.972±0.108 g/cm 2, p<0.0001). T score and Z score showed lower values compared to healthy controls (lumbar spine: T=-1.6±1.1 vs -0.7±1.1, p<0.0001; Z=0.2±1.1 vs 0.6±0.2, p<0.05 and total hip: T=-1.7±0.7 vs -0.8±0.3, p<0.0001; Z=-0.4±0.3 vs -0.1±0.7, p<0.03, respectively). In addition, BMD at lumbar spine and total hip was lower in patients with "late" NVC pattern than in those with "early" and "active" patterns (lumbar spine 0.962±0.146 g/cm 2 vs 0.999±0.124 g/cm 2 and 0.981±0.161 g/cm 2 ; total hip 0.771±0.101 g/cm 2 vs 0.839±0.081 g/cm 2 and 0.841±0.161 g/cm 2, all p<0.05, respectively "late" vs "active" and "early" pattern). 25(OH)D levels [19.4±13 ng/mL vs 20.3±12 ng/mL] and bone metabolic parameters [Dpd 12.6±3.9 nmol/mol vs 11.2±3.6 nmol/mol and NTx 49.6±26.8 nmol/mol vs 45.6±24.3 nmol/mol] were found lower in winter vs summer. On the contrary, the bone resorption parameters [OC 10.2±4.2 μg/L vs 12.1±2.8 μg/L and bALP 10.7±4.2 μg/L vs 12.5±4.5 μg/L] were found significantly higher in winter as compared to summer (p 0<0.05).No significant correlations were found between 25(OH)D levels or other boneparameters between winter and summer. Conclusions: The present study reports the presence of reduced values of BMD and bone remodeling markers in patients with SSc. On the basis of their NVC patterns, this difference was more marked in the "late" pattern group and in winter (low [25(OH)D]. A possible role of diffuse tissue ischaemia as a consequence of the SSc microangiopathy/fibrosis, but also other factors may contribute to this 2 . Disclosure of Interest: None Declared